Fraværsgrensen i videregående skole Perspektiver, konsekvenser og erfaringer - Rogstad, Jon (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"An absence limit for upper secondary school in Norway was introduced in 2016. The objective was to get more students to attend school more regularly. There were considerable protests at the time - especially from the students - and now five years on, the question is: Has the absence limit helped? Has attendance increased? And if so, at what cost? The Absence Limit in Upper Secondary School. Viewpoints, Outcomes and Experiences presents the results of a comprehensive evaluation of the new ordinance from three perspectives: the students', the schools', and their support networks'. The book starts with the main characters - the students - and then looks at the schools, and finally at the various support persons in students' lives. Three questions structure the book: To what extent has absenteeism among different groups of students been reduced as a result of the absence limit? From a practical standpoint, how is the absence limit enforced by school administrators and teachers? And how do doctors and other support persons follow up students with high absenteeism? This book is relevant for teachers, school administrators, students, politicians, researchers, and anyone interested in Norwegian educational policy. "